Responsible and adaptive robots in care home settings: an implementation framework analysis of a workshop with public and professionals - Boudouraki, Andriana; Waheed, Maria; Mestre, Rafael; Landowska, Aleksandra; Georgara, Athina; Deshmukh, Jayati; Singh, Lokesh; Abioye, Ayodeji O.; Viet Tuyen, Nguyen Tan; Dong, Yi; Ao, Shuang; Price, Dominic; et al. (Frontiers in Robotics and AI, 2025)
As populations grow, research looks to emerging adaptive technologies for the urgent challenge in providing suitable care for older adults. Drawing on implementation science, we conducted a holistic examination looking at broader, contextual factors relating to the acceptability of robotics and sensor technologies in care homes. We held a workshop that brought together members of the public and researchers with experience in care home, to try such technologies and discuss their application in different care home scenarios. Using the NASSS framework, we examine acceptability through the angles of technology, condition, adopters, value proposition, organisation, wider context, and sustainability. While both groups of participants share concerns about the negative impacts of robotics on the quality of care, we also uncovered additional areas of further consideration relating to tensions between stakeholders and constraints around material resources, culture, processes and regulatory considerations.